Soybean Looper Chrysodeixis includens (Walker) (Insecta: Lepidoptera: Noctuidae) - Ethan T. Carter; Jennifer Lynn Gillett-Kaufman (EDIS)
The soybean looper, Chrysodeixis includens (Walker), is a light to dark green caterpillar which derives its name from its preferred host plant (soybean, Glycine max) and the looping movement it makes while in motion.  Includes: Introduction - Distribution - Description and Life Cycle - Hosts - Damage and Economic Importance - Management - Selected References